Calculating Foreign Direct Investment in the Information and Communication Technology Sector in Egypt - Robertson, Geoffrey (World Bank, Washington, DC, 2013)
This report is part of an ongoing study of the measurement of foreign direct investment (FDI) in the information and communication technology (ICT) sector of Egypt's economy. This report forms part of the second amendment to a reimbursable technical assistance (RTA) program delivered by the Global Information and Communication Technology (GICT) department of the World Bank to the Information Centre of the Ministry of Communication and Information Technology (MCIT-IC) of the government of Egypt. This report outlines the results of a several visits to the region, a survey conducted, and methods of data collection. The objectives were: to analyze the new results of the FDI questionnaire and make recommendations to refine the methodology and sampling framework; to generate an estimate of the true level of FDI in Egypt's ICT sector, and to continue work towards establishing an ongoing process for the regular data collection and reporting of FDI data by providing training and relevant tools, in collaboration with relevant ministries and other institutions.